2021
DOI: 10.1007/s00170-021-06997-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the fiber orientation on the tensile and flexural behavior of continuous carbon fiber composites made via fused filament fabrication

Abstract: Recent years have seen the wide diffusion of composite materials in many manufacturing fields and the rapid evolution of additive manufacturing. Lately, these technologies have been combined practically allowing the fabrication of continuous-fiber reinforced polymer parts via 3D-printing. This topic is gaining attention both in the research community and among industrial users. Because of their novelty, such manufacturing methods are, however, still not thoroughly understood, and their performance limits have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 35 publications
3
31
1
Order By: Relevance
“…7). The results were in contrast to those obtained in [11]. The specimen with fibres oriented at 0° exhibited optimal performances during the tensile test.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…7). The results were in contrast to those obtained in [11]. The specimen with fibres oriented at 0° exhibited optimal performances during the tensile test.…”
Section: Discussioncontrasting
confidence: 96%
“…In particular, it was observed that samples with fiber along 0 and 90° has higher stiffness and resistance to bearing strength, this phenomenon is coherent with the results obtained by [11] in case of tensile test. However, respect to [11] better results have been achieved with Test 0-90 mixed or simple comparing with results of Test 0°; the reason is caused by the stress distribution that in pin bearing is not constant but varies from zero at the sides of the hole to a maximum behind the pin. In accordance with [11] no significative results have been observed for mixed or single configuration.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations